2021
DOI: 10.1039/d0qm00874e
|View full text |Cite
|
Sign up to set email alerts
|

Smart active antibiotic nanocarriers with protease surface functionality can overcome biofilms of resistant bacteria

Abstract: We developed a novel active nanocarrier of common antibiotics, which can efficiently degrade biofilms of resistant bacteria and bypass their defences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Treating bacterial infections with species demonstrating antibiotic resistance to the chosen antibiotic is often hindered due to the ability of certain bacteria to grow biofilms where they can effectively hide and resist the antibiotic action. Weldrick et al 147 reported an innovative solution for overcoming both antibiotic resistance and biofilm formation by designing active antibiotic nanocarriers with a protease surface functionality on the shellac nanoparticles loaded with an antibiotic. The cationic protease coating, whilst allowing electrostatic adhesion of the nanoparticle to the cell, simultaneously also degrades the biofilm and helps the active nanocarriers to reach the entrapped bacterial cells (Fig.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating bacterial infections with species demonstrating antibiotic resistance to the chosen antibiotic is often hindered due to the ability of certain bacteria to grow biofilms where they can effectively hide and resist the antibiotic action. Weldrick et al 147 reported an innovative solution for overcoming both antibiotic resistance and biofilm formation by designing active antibiotic nanocarriers with a protease surface functionality on the shellac nanoparticles loaded with an antibiotic. The cationic protease coating, whilst allowing electrostatic adhesion of the nanoparticle to the cell, simultaneously also degrades the biofilm and helps the active nanocarriers to reach the entrapped bacterial cells (Fig.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…16E and F). 147 This concept was demonstrated by encapsulating Penicillin G and Oxacillin into shellac NPs, subsequently coated with the serine Weldrick et al 154 tested the performance of a similar innovative nanotechnological approach on S. aureus, where the results showed a boost in the biomass reduction of the bacterial biofilms compared to treatment with free clindamycin as well as with conventionally used antibacterial agents (cetrimide, benzalkonium chloride, povidone-iodine (PVP-I), and chloroxylenol).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…In another approach, the nanocarrier-based drug combination therapy has been widely applied for the treatment of biofilm infections by co-delivering antibiotics and biofilmdispersing enzymes, which are capable of degrading EPS components, such as proteins, eDNA, polysaccharides, or quorum-sensing molecules (Table 4) [136][137][138][139]. The dispersing compounds could revert the biofilm bacteria back to their planktonic growth mode, rendering bacteria susceptible to conventional antibiotics.…”
Section: Codelivery Platforms For Combination Antibiotic Therapymentioning
confidence: 99%
“…Some of these cationic nanoparticle formulations rely on electrostatic attraction with the negatively charged cell walls of microbial cells. Recently, active nanocarriers of both antibiotic and antifungal agents were developed with protease coating that can digest their way through biofilms delivering their payload to the embedded microbial cells [27][28][29]. However, in antimould applications, the strategy of using solely such electrostatic binding to the mould can be challenging due to the presence of other anionic species in the hyphae immediate environment which can render the treatment ineffective.…”
Section: Introductionmentioning
confidence: 99%